Our data, ourselves: Participation, justice, and alternative futures of data sovereignty in India - Sagnik Dutta; Suruchi Mazumdar (Big Data & Society)
Scholars have used the term data colonialism to designate the extractive, asymmetrical relationship between Big Tech corporations and countries in the global South. However, there is scant attention paid to how data colonialism might be reconfigured in the everyday life of postcolonial states. This paper explores how civil society actors and digital rights activists in India challenge data colonialism by articulating new meanings of data sovereignty within the larger context of the postcolonial Indian state's relationship to global Big Tech corporations. Drawing on a series of roundtable conversations with academics and digital rights activists and podcast ethnography, this paper proposes a grassroots activism-based framework of data sovereignty and challenges a state-centric, neocolonial conception of data sovereignty. First, this paper outlines resistance to data colonialism posited by digital rights activists, civil society actors and social movements through commitment to data accountability, transparency and justice. Second, we explore bottom-up negotiations that challenge top-down approaches to data ownership and data sovereignty. Activists highlighted instances of grassroots-led civil society activism in India that emphasise collective mobilisation by citizens to make governments accountable and transparent with regard to their data and thereby articulated a concept of data ownership beyond indigenous conceptions of community. These included initiatives that enhance transparency of public services for citizens, citizen collectives for migrant workers and concerted efforts of workers against state surveillance aided by domestic technological startups. We advance scholarship on data colonialism and data sovereignty by focusing on novel imaginaries of data in a postcolonial context.